Recycling endosomes associate with Golgi stacks in sea urchin embryos - Fujii, Syara (Commun Integr Biol, 2020)
The trans-Golgi network (TGN) and recycling endosome (RE) have been recognized as sorting centers, the former for newly synthesized and the latter for endocytosed proteins. However, recent findings have revealed that TGN also receives endocytosed materials and RE accepts newly synthesized proteins destined to the plasma membrane. Recently, we reported that in both Drosophila and microtubule-disrupted HeLa cells, REs are associated with the trans-side of Golgi stacks. REs are highly dynamic: their separation from and association with Golgi stacks are often observed. Importantly, a newly synthesized cargo, glycosylphosphatidylinositol-anchored-GFP was found to be concentrated in Golgi-associated REs (GA-REs), while another cargo VSVG-GFP was excluded from GA-REs before post-Golgi trafficking to the plasma membrane. This suggested that the sorting of cargos takes place at the interface of Golgi stacks and GA-REs. In this study, we demonstrated that REs could associate with Golgi stacks in sea urchin embryos, further indicating that the association of REs with Golgi stacks is a well-conserved phenomenon in the animal kingdom.